Automatic Prejudice and Weapon Identification: A Study with Students and Police Officers - Dantas, Gilcimar Santos (Race and social problems, 2023)
The objective of this study was to explore police officers’ beliefs, meaning whether a “crime priming” is capable of showing automatic prejudice in the identification of weapons and whether a crime reduction priming can mitigate it, seeking to understand which processes can make the expression of racism more evident. With that we conducted two experiments with police officers (N = 80) and university students (N = 77) randomly allocated to an experimental group subjected to crime priming. In the second experiment we submitted the groups to a criminal's rehabilitation priming. In Study 1, crime priming contributed to shorter response times for both guns and tools preceded by a black individual's face. Under rehabilitation priming, participants showed longer response times for both guns and tools, an effect intensified when preceded by a black individual's face. With regard to hits, more hits occurred for guns than for tools, a result unaffected by the experimental manipulation. With regard to hits, more hits occurred for gun than for tool, a result unaffected by the experimental manipulation. In the 500 ms time-limited phase (study 2), there was no effect of the priming types on response times, with only a higher hit rate for black individual's faces. With that, questions about the importance of replicating WIT results in a more mixed sample in which both the control group and the police officers group can be considered as coming from minorities (i.e. blacks and latinx).